ERECTOR SPINAE PLANE BLOCK IN THORACOTOMY SURGERY - Novara, Tendi; Cahyono, Iwan Dwi; Hapsari, Rania Adeastri (JAI (Jurnal Anestesiologi Indonesia), 2021)
Background: Post-thoracotomy pain management remains a major challenge in anesthesia. Thoracic epidural and paravertebral blocks are effective but technically demanding. The erector spinae plane (ESP) block offers a simpler and safer alternative for postoperative analgesia. This case report presents the anesthetic and analgesic management using ESP block in a patient undergoing thoracotomy decortication.Case: A 60-year-old male with spontaneous right pneumothorax and pulmonary atelectasis underwent thoracotomy decortication under general anesthesia. An ultrasound-guided ESP block was performed at T5–T6 using 0.25% levobupivacaine (20 mL). Intraoperative hemodynamics were stable, and the patient was extubated 14 hours postoperatively. Pain scores remained low without additional opioids. No complications were observed during postoperative monitoring.Discussion: Spontaneous pneumothorax and pulmonary atelectasis frequently necessitate surgical intervention, demanding complex anesthetic management. This patient presented with a right-sided pneumothorax, compounded by atelectasis resulting from prior trauma. After the surgery. The patient underwent an erector spinae plane (ESP) block at T5-T6 under general anesthesia for postoperative analgesia. Postoperatively, the patient exhibited satisfactory oxygenation, low pain scores, and no complications associated with the ESP block, indicating effective pain control.Conclusion: This case report illustrates that an ESP block administered postoperatively can offer effective analgesia management for patients with spontaneous pneumothorax and pulmonary atelectasis undergoing decortication thoracotomy. This strategy not only ensures adequate pain relief but also facilitates early mobilization and reduces postoperative opioid use. These findings endorse the integration of the ESP block into a multimodal anesthetic approach for thoracic surgery.